Using principal trabecular orientation to differentiate joint loading orientation in the 3rd metacarpal heads of humans and chimpanzees. Issue 113 (December 2017) - Barak, Meir M.; Sherratt, Emma; Lieberman, Daniel E.
Abstract: If Wolff's law is valid, then quantifying the three-dimensional architecture of trabecular bone, specifically 3D principal trabecular orientation (3D-PTO), can reveal joint loading direction among different taxa. This study measured the architecture of trabecular bone in the 3rd metacarpal head of humans and chimpanzees, and then tested their association with expected joint loading direction. We postulate that since chimpanzees, unlike humans, directly load their metacarpal bones during knuckle-walking, trabecular structure in the dorsal aspect of the 3rd metacarpal head will be significantly more organized and robust in chimpanzees. To test this hypothesis, we micro-CT scanned the 3rd metacarpal from 11 chimpanzees and 12 humans. Three 6 mm volumes of interest (VOI; palmar, center and dorsal) were selected and trabecular bone properties and 3D-PTO were measured. The results revealed many similarities between humans and chimpanzees: in both taxa the dorsal VOI demonstrated the lowest bone volume fraction (BV/TV), the most rod-like trabecular structure, the fewest and thinnest trabeculae, and low organization of the trabecular architecture (degree of anisotropy). Nevertheless, 3D-PTO in the dorsal VOI differed significantly between humans and chimpanzees. While 3D-PTO in humans was clustered together and aligned nearly along the bone long axis, in chimpanzees 3D-PTO was divided into two distinct groups and aligned with an angle toward either the medial or lateral orientations. Our results suggest that loading effects on trabecular bone properties such as BV/TV might be partially constrained by genetic factors. On the other hand, 3D-PTO is continually affected by active loading (i.e., modeling) and thus may serve as a useful tool to infer differences in joint loading directions.